2018
DOI: 10.1155/2018/3583921
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Pretreatment Protects H9c2 Cells against Anoxia/Reoxygenation Injury: Involvement of the Translocation of Bcl‐2 to Mitochondria Mediated by 14‐3‐3η

Abstract: Tanshinone IIA is an important component that is isolated from danshen (Salvia miltiorrhiza), which is known to be beneficial for cardiovascular health. In this study, we determined the effects of Tanshinone IIA and its underlying mechanisms of action in an anoxia/reoxygenation (A/R) cell line model. Prior to inducing A/R injury, rat cardiomyocyte-derived cell line H9c2 was stimulated with 8 μM of Tanshinone IIA for 48 hours. When compared with the A/R group, the Tanshinone IIA treatment significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
5
23
0
Order By: Relevance
“…In previous studies, we confirmed that 1 mM Dox for 24 h could induce myocardial cytotoxicity (He et al, 2018). Cell viability and LDH leakage generally serve as indexes of cell injury (Zhang et al, 2018). The MTS assay results showed that the viability of the Dox groups was significantly lower than that of the control group, and LDH activity of the Dox groups was significantly higher relative to that observed in the control group (P < 0.01, Figures 4A, B).…”
Section: Dox Toxicity Could Damage Huvecs Cellssupporting
confidence: 74%
“…In previous studies, we confirmed that 1 mM Dox for 24 h could induce myocardial cytotoxicity (He et al, 2018). Cell viability and LDH leakage generally serve as indexes of cell injury (Zhang et al, 2018). The MTS assay results showed that the viability of the Dox groups was significantly lower than that of the control group, and LDH activity of the Dox groups was significantly higher relative to that observed in the control group (P < 0.01, Figures 4A, B).…”
Section: Dox Toxicity Could Damage Huvecs Cellssupporting
confidence: 74%
“…14-3-3 is the molecular target of many active ingredients of plants. We have confirmed that 14-3-3 assists PKCε, Bcl-2, and other functional proteins to locate to mitochondria and protect cardiomyocytes and vascular endothelial cells against multiple injuries [7,9,[40][41][42][43]. Further studies are needed to define specific mechanism(s) of action for Cap-activated 14-3-3η in anoxia and A/R injured cardiomyocytes.…”
Section: Discussionsupporting
confidence: 53%
“…Functionally, together with partner proteins, 14-3-3 regulates phosphorylation and dephosphorylation, kinase activity, and cellular location of proteins that may participate in cell proliferation, differentiation, survival, transformation, and apoptosis [37,38]. Our previous study demonstrated that 14-3-3η is activated in ischemia/hypoxia injury while 14-3-3γ activation is linked to infectious/inflammatory lesions [7][8][9]39]. 14-3-3 is the molecular target of many active ingredients of plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis-Related Genes. Bcl-2 [38], BAX [39], and caspase-3 [40,41] have been reported to be associated with oxidative stress and apoptosis. Infrasound treatment reduced relative mRNA level of Bcl-2 and a sharp increase in relative mRNA levels of bax and caspase-3.…”
Section: The Effects Of Thsg On Relative Mrna Levels Ofmentioning
confidence: 99%